أساليب الاتصال بالآخر في القرآن الكريم من منظور عقائدي - Nouna Sammari; Zahir Hanuf (Akidah and Religion Studies Programme ,Faculty of Leadership and Management, USIM, 2024)
E-Proceedings Of The International Conference On Aqidah, Religions And Social Sciences (SIGMA10) “ Towards Peaceful Co-Existence And Excellence Of Ummah : An Implication Of Rahmatan Lil’Alamin” Akidah and Religion Studies Programme, Faculty of Leadership and Management 4th November 2020